DINAMIKA DAN TANTANGAN DAKWAH ISLAM DI ERA MODERN - Nasution, Sintiana; Zainal Efendi Hasibuan (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2024)
Islamic da’wah in the modern era faces various complex challenges due to the rapid advancements in technology, globalization, and social changes. One of the main issues in da’wah today is how to deliver Islamic messages that remain relevant and are accepted by a society that is increasingly diverse and influenced by external factors. The use of digital media, particularly the internet and social media, has become a key strategy in spreading da’wah, but it also presents challenges related to the spread of inaccurate information and differing interpretations of Islamic teachings. This research uses a qualitative approach with literature review and in-depth interviews with several da’wah practitioners and religious leaders. The findings show that Islamic da’wah today is largely conducted through digital platforms, which reach a global audience, but still faces challenges in maintaining authenticity and the diversity of Islamic interpretations. Effective da’wah requires a contextual and adaptive approach to the changing times while upholding the core principles of Islam. The conclusion of this study is that Islamic da’wah must continue to innovate by leveraging digital technology, while ensuring that universal Islamic values are upheld, so that the message can be widely accepted and understood without losing the essence of the true religious teachings.